2011
DOI: 10.1021/jf200964u
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological, Structural, and Drug Delivery Properties and Applications of 1,3-β-Glucans

Abstract: 1,3-β-Glucans are a class of natural polysaccharides with unique pharmacological properties and the ability to form single- and triple-helical structures that can be formed into resilient gels with the application of heat and humidity. The pharmacological capabilities of 1,3-β-glucans include the impartation of tumor inhibition, resistance to infectious disease, and improvements in wound healing. Curdlan is a linear 1,3-β-glucan that has been used extensively to study the nature of these helical structures and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(59 citation statements)
references
References 134 publications
2
57
0
Order By: Relevance
“…Senni et al [47] have demonstrated that deep sea hydrothermal bacteria glycosaminoglycans, resembling hyaluronan, can improve collagen aggregation and potently collagen deposition. ␤-Glucan is known to be a structure forming agent, creating helical micelles with other molecules [48], which could also act as an aggregating agent for collagen molecules. Independently of the collagen deposition capacity, ␤-glucan as well as several glycosaminoglycans has been shown to increase cell collagen biosynthesis [22][23][24], which can thus also induce an increase in tissue thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Senni et al [47] have demonstrated that deep sea hydrothermal bacteria glycosaminoglycans, resembling hyaluronan, can improve collagen aggregation and potently collagen deposition. ␤-Glucan is known to be a structure forming agent, creating helical micelles with other molecules [48], which could also act as an aggregating agent for collagen molecules. Independently of the collagen deposition capacity, ␤-glucan as well as several glycosaminoglycans has been shown to increase cell collagen biosynthesis [22][23][24], which can thus also induce an increase in tissue thickness.…”
Section: Discussionmentioning
confidence: 99%
“…A non-toxic and super-absorptive hydrogel made up of pullulan (glucan polysaccharide), a biosynthetic derivative of starch, has been effectively used for antibacterial or antimycotic drugs released at wound site [238]. Different types of d -glucans derived from yeast, grain, and fungi have been utilized to prepare the gel structures which support effective wound healing with lowered skin irritation [239]. A dextran biomaterial, Carboxymethyl Benzylamide Sulfonate Dextran (CMDBS), has structural similarity with the glycosaminoglycan heparin, and is well-known for not only stimulating wound healing but also for being effective in controlling Staphylococcus aureus biofilm formation [240].…”
Section: Biomaterials and Nanobiomaterials Used For Several Scaffomentioning
confidence: 99%
“…In Eastern culinary tradition, eating mushrooms (which contain large quantities of soluble -glucan in their fruiting bodies) has long been recognized as healthy, and four pharmaceutical preparations, based on mushroom extracts, have been registered as drugs in Japan (Hyodo et al, 2005). In the Western world several clinical trials (Babineu et al, 1994;Weitberg, 2008;Spruijt et al, 2010) proved the beneficial properties of WGP and PGG glucans, which are still waiting to be registered as drugs (Vetvicka, 2011;Lehtovaara & Gu, 2011). The following therapeutic activities of yeast -glucan are well-established in treating the following conditions: post-surgical infections, hospital pneumonia, acute renal failure (Koc et al, 2011), pressure ulcers (bed sores), wound healing (surgical and as result of injury, Spruijt et al, 2010) and burns caused by heat, UV or X-ray radiation.…”
Section: Medicinal Application Of Native and Chemically Modified Formmentioning
confidence: 99%